China's Belt and Road (BRI) Policy for Trade Interests in Indonesia - Riska, Riska Fatmala Dewi (Universitas Negeri Surabaya, 2024)
In promoting international trade within Indonesia, the government relies on Law Number 7 of 2014 concerning Trade. This legislation serves as a foundational framework for facilitating trade activities and addressing related issues. As part of efforts to bolster infrastructure development amidst financial constraints, Indonesia has turned to initiatives such as the Chinese Silk Road, or Belt and Road Initiative (BRI). This strategic partnership aims to enhance Indonesia's infrastructure capabilities, particularly in light of budgetary limitations that have hindered optimal development. However, the implementation of BRI projects has sparked concerns and varying interpretations, particularly regarding the potential risks of falling into a